Populism and Euroscepticism in Podemos and in the Five Star Movement. Faraway, so close? - Damiani, Marco; Viviani, Lorenzo (PARTECIPAZIONE E CONFLITTO, 2019)
Since the Nineties the crisis of traditional political families has become particularly intense in the democracies of Southern Europe, with an increase in electoral volatility, the contraction of party membership, and crises of confidence as well as of electoral consensus. In these democracies, alongside the traditional parties of the twentieth century, a generation of new political parties was born that reject the right/left division, politicizing a new cleavage between the low and the high of society, or – better – between the people and the elite. In Spain and Italy, the anti-political-establishment supply side is provided expecially by two new movement-parties, Podemos and the Five Star Movement. This article focuses on the comparison between these two new political parties, highlighting differences and analogies in terms of policy, identity, and organization. The research hypothesis developed in this paper refers to the different form and identity in which populism is expressed in the two national cases. From the methodological point of view, the comparison between the two parties will be conducted through the analysis of the text of the electoral programs of the two different political organizations in the European elections in the period running from 2014 to 2017.